Simulation Analysis and Modeling of New Type Cam Mechanism based on Pro / E and ADAMS - He Haiqin; Li Yanping; Chang Yong (Jixie chuandong)
The virtual prototyping modeling of new typed disc cam mechanism with straight moving negative radius roller follower is created by using Pro / E and ADAMS. The flexibility treatment to roller follower is carried out by using the ADAMS / Flex module and the rigid- flexible coupled model is built,the output response motion curve of flexible follower is obtained. Comparing the output response of flexible follower with rigid follower,it directly reflects the deviation of the motion rule.